Perioperative Management of Direct Oral Anticoagulants (DOACs): A Systemic Review - Tagore Sunkara; Emmanuel Ofori; Vadim Zarubin; Megan E. Caughey; Vinaya Gaduputi; Madhavi Reddy (SAGE Publishing, 2016)
Direct oral anticoagulants (DOACs) are in wide use among patients requiring both short- and long-term anticoagulation, mainly due to their ease of use and the lack of monitoring requirements. With growing use of DOACs, it is imperative that physicians be able to manage patients on these medications, especially in the perioperative period. We aim to provide guidance on the management of DOACs in the perioperative period. In this review, we performed an extensive literature search summarizing the management of patients on direct-acting anticoagulants in the perioperative period. A total of four direct-acting oral anticoagulants were considered appropriate for inclusion in this review. The drugs were dabigatran etexilate mesylate (Pradaxa), rivaroxaban (Xarelto), apixaban (Eliquis), and edoxaban (Savaysa). Management of patients on DOACs in the perioperative period involves an assessment of thromboembolic event risk while off anticoagulation compared to the relative risk of bleeding if such drug is continued. DOACs may not need to be discontinued in minor surgeries or procedures, and in major surgeries, they may be discontinued hours prior depending on drug pharmacokinetics and renal function of the patients.